Music of the Spheres and the Dance of Death : Studies in Musical Iconology - Meyer-Baer, Kathi, 1892-1977 (Book collections on Project MUSE., 1970)
The roots and evolution of two concepts usually thought to be Western in origin-musica mundana (the music of the spheres) and musica humana (music's relation to the human soul)-are explored. Beginning with a study of the early creeds of the Near East, Professor Meyer-Baer then traces their development in the works of Plato and the Gnostics, and in the art and literature of the Middle Ages and the Renaissance. Previous studies of symbolism in music have tended to focus on a single aspect of the problem. In this book the concepts of musica humana and musica mundane are related to philosophy, ae.